Seasonal Characteristics of Long-Range Transport and Potential Associated Sources of Particulate Matter (Pm10) Pollution at the Station Elk, Poland, on 2021-2022 Data - S. Abdo; Y. Koroleva (Russian Geographical Society, 2023)
The current study aimed to determine the potential sources of distant emissions of PM10 particles that significantly affect PM10 levels at a given site in southeastern Baltic. The EEA Air Quality Monitoring Station in Elk City, northeastern Poland, was selected for this study. This station is located approximately 50 km from the border of the Russian exclave (Kaliningrad Region). In this study, the NOAA HYSPLIT_4 trajectory model, potential source contribution function (PSCF), and concentration-weight trajectory (CWT) were employed to investigate the origin of the measured PM10 mass at a receptor site. PSCF and CWT utilize back-trajectory analysis and Lagrangian particle dispersion simulations to reconstruct the advection pathways of air masses arriving at the site. These reconstructed retroplumes provide detailed information regarding the geographic locations traversed by polluted air masses on their way to the receptor. By integrating trajectory information with concurrent pollutant concentration data, the PSCF and CWT enable the identification of potential source regions and quantification of their impact on the observed atmospheric levels. From January 1, 2021, to December 31, 2022, at 200 m the 72h backward trajectories of air masses entering the receptor point were calculated and categorized by clustering them into 5-4-4-5 clusters. Subsequently, the PM10 levels at the Elk site associated with each air mass cluster were examined during the observation period. The seasonal variation in PM10 was generally characterized by a peak in winter and minimum values in summer. PM10 was lower during warmer periods, particularly during summer, and significantly, higher concentrations were observed during colder periods. Cluster analyses showed that airflow followed a seasonal pattern, with different results obtained in different seasons. According to the PSCF and CWT results, in winter and spring, the receptor site was influenced more by long-range PM10 pollution, particularly from heavily industrialized areas in ...